Reduced plasmablast frequency is associated with seronegative myasthenia gravis - Guptill, Jeffrey T. (Muscle Nerve, 2020)
INTRODUCTION/AIM: The immunopathology of autoimmune seronegative myasthenia gravis (SN MG) is poorly understood. Our objective was to determine immune profiles associated with a diagnosis of SN MG. METHODS: We performed high-dimensional flow cytometry on blood samples from SN MG patients (N=68), healthy controls (N=46), and acetylcholine receptor antibody (AChR+) MG patients (N=27). We compared 12 immune cell subsets in SN MG to controls using logistic modeling via a discovery-replication design. An exploratory analysis fit a multinomial model comparing AChR+ MG and controls to SN MG. RESULTS: An increase in CD19(+)CD20(-)CD38(hi) plasmablast frequencies was associated with lower odds of being a SN MG case in both the discovery and replication analyses (discovery p-value=0.0003, replication p-value=0.0021). IL-21 producing helper T cell frequencies were associated with a diagnosis of AChR+ MG (p=0.004). DISCUSSION: Reduced plasmablast frequencies are strongly associated with a SN MG diagnosis and may be a useful diagnostic biomarker in the future.